Pelatihan Penggunaan Aplikasi Hiilsinergi dalam Meningkatkan Efisiensi dan Efektivitas Pengelolaan Organisasi di Era Digital - Dinata, Muhammad Imam; Idham, Idham; Rahman, Arif; Yusuf, Siti Agrippina Alodia; Sulistianingsih, Nani (Universitas Negeri Gorontalo, 2026)
The rapid development of information technology has encouraged various sectors, including non-formal education, to utilize digital technology as a medium for improving services and strengthening institutional branding. According to APJII data in 2024, 79.5% of Indonesia's population has accessed the internet, making the use of websites as an information medium increasingly important for training and course institutions (LKP). LKP Berlian Education continues to face challenges in providing adequate digital facilities, including the absence of a website as a platform for publication and information services. This community service program aims to enhance the competencies of LKP participants in creating and managing websites as an effort to strengthen branding and deliver information quickly, accurately, and online. The implementation methods include technical guidance, training, mentoring, and forum group discussions. Evaluation was conducted through pretest and posttest using a nominal scale, as well as a service satisfaction questionnaire using a Likert scale. The results indicate a significant improvement in participants’ abilities to understand basic website concepts, use the WordPress CMS, and manage digital content. Overall, this community service activity has proven effective in improving the digital competencies of LKP Berlian Education participants, particularly in the creation and management of websites as a means of institutional branding and information services